Empress Adelheid and Countess Matilda - Nash, Penelope. author. aut Link
XXXI, 292 p. 8 illus., 1 illus. in color.
Keywords: This book compares two successful, elite women, Empress Adelheid (931-999) and Countess Matilda (1046-1115), for their relative ability to retain their wealth and power in the midst of the profound social changes of the eleventh century. The careers of the Ottonian queen and empress Adelheid and Countess Matilda of Tuscany reveal a growth of opportunities for women to access wealth and power. These two women are analyzed under three categories: their relationships with family and friends, how they managed their property (particularly land), and how they ruled. This analysis encourages a better understanding of gender relations in both the past and the present. .